A dynamic model for firm-response to non-credible incentive regulation regimes. (March 2016) - Agrell, Per J.; Grifell-Tatjé, Emili
Abstract: Economic network regulation increasingly use quantitative performance models (from econometrics and engineering) to set revenues. In theory, high-powered incentive regulation, such as revenue-caps, induces firms to cost-efficient behavior independent of underlying model. However, anecdotal evidence shows regulated firms occasionally maintaining cost-inefficiency under incentive regulation even under slumping profitability. We present a model for firm-level efficiency under a regime with a probability of failure explaining this phenomenon. The model is based on the hypothesis that the regulatory choice of method can be associated with intrinsic flaws leading to judicial repeal and replacement of it by a low-powered regime. The results show that the cost efficiency policy is proportional to the type of firm (cost of effort), value of time (discount factor) and the credibility of the method (risk of failure). A panel data set for 2000–2006 for 128 electricity distributors in Sweden is used to validate the model predictions (radical productivity slowdown, failing profitability and efficiency) at the launch and demise of a non-credible regulation method. The work highlights the fallacy of viewing incentive regulation as a method-independent instrument, a result applicable in any infrastructure regulation. Abstract : Highlights: Incentive regulation relies on fixed revenue for operators. In existing theory the efficiency-inducing effect is model-independent. A dynamic game exposes the firm to a regulation that may fail. One optimal policy is to pad cost and wait for the failure. The Swedish DSOs show this policy 2003–2006, when the regime failed.